2023
DOI: 10.1038/s41598-023-33581-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium nanoparticles on biological and morphofunctional parameters of barley seeds (Hordéum vulgáre L.)

Abstract: The purpose of this work was to study the effect of selenium nanoparticles (Se NPs) on the biological and morphofunctional parameters of barley seeds (Hordéum vulgáre L.) We used seeds of Hordéum vulgáre L. with reduced morphofunctional characteristics. For the experiment, Se NPs were synthesized and stabilized with didecyldimethylammonium chloride. It was found that Se NPs have a spherical shape and a diameter of about 50 nm. According to dynamic light scattering data, the average hydrodynamic radius of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Another important area of application of nanomaterials, in particular, manganese nanoparticles and their oxides, is agriculture [31][32][33]. A large number of research papers are devoted to the study of the influence of nanoscale oxide forms on the morphofunctional characteristics of agricultural plants [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. For example, the work of Margenot et al [49] shows that the addition of copper oxide (CuO) nanoparticles increases the diameter of the roots of lettuce seedlings by 52% and the diameter of carrot seedlings by 26%.…”
Section: Introductionmentioning
confidence: 99%
“…Another important area of application of nanomaterials, in particular, manganese nanoparticles and their oxides, is agriculture [31][32][33]. A large number of research papers are devoted to the study of the influence of nanoscale oxide forms on the morphofunctional characteristics of agricultural plants [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. For example, the work of Margenot et al [49] shows that the addition of copper oxide (CuO) nanoparticles increases the diameter of the roots of lettuce seedlings by 52% and the diameter of carrot seedlings by 26%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in heat-stressed tomato plants, the concentrations of Se NPs with the best results on growth parameters were found to be 5 and 10 ppm, while 20 ppm showed signs of phytotoxicity 30 . In Barley ( Hordeum vulgare ) nanoprimed seeds with Se NPs, the best treatment for the germination quality in Petri dishes was also 5 ppm, while 10 ppm resulted in the highest number and thickness of roots 46 . In accordance with these studies, we found similar concentrations of Se NPs to have the best results in our nanopriming experiment for tomato seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The application of Trichoderma strains on seeds promotes germination and seedling development [66,174,175]. The chemically synthetized SeNPs, stabilized with didecyldimethylammonium chloride, improved the germinability and germination of barley seeds (Hordéum vulgáre L.) with impaired morphofunctional characteristics due to 10 years of storage [176]. The trichogenic SeNPs should have a better effect as biostimulants of seed germination due to the combined effect of SeNPs and the bio-corona consisting of proteins and metabolites from biostimulant Trichoderma strains.…”
Section: Vigna Radiatamentioning
confidence: 99%